Ecological Research of the Kő-hegy in Budaörs by Innovative Developmental Possibilities - Majnár, Klaudia (International Journal of Engineering and Management Sciences, 2017)
The function of the environmental education is essential for the sake of the natural environment. The amazing view from Kő-hegy is noticeable, and it must be preserved for the next generations. Today to achieve the environmental conscious forming aspects it’s necessary to develop modern applications and environmental education. The aim of research is the innovative development to sustainability